Genetic dissection of wheat uppermost-internode diameter and its association with agronomic traits in five recombinant inbred line populations at various field environments - Hang LIU; Hua-ping TANG; Wei LUO; Yang MU; Qian-tao JIANG; Ya-xi LIU; Guo-yue CHEN; Ji-rui WANG; Zhi ZHENG; Peng-fei QI; Yun-feng JIANG; Fa CUI; et al. (Journal of Integrative Agriculture, 2021)
Uppermost-internode diameter (UID) is a key morphological trait associated with spike development and yield potential in wheat. Our understanding of its genetic basis remains largely unknown. Here, quantitative trait loci (QTLs) for UID with high-density genetic maps were identified in five wheat recombinant inbred line (RIL) populations. In total, 25 QTLs for UID were detected in five RIL populations, and they were located on chromosomes 1A, 1D (3 QTL), 2B (2), 2D (3), 3B, 3D, 4A, 4B (3), 4D, 5A (5), 5B (2), 6B, and 7D. Of them, five major and stable QTLs (QUid.sau-2CN-1D.1, QUid.sau-2SY-1D, QUid.sau-QZ-2D, QUid.sau-SC-3D, and QUid.sau-AS-4B) were identified from each of the five RIL populations in multiple environments. QUid.sau-2CN-1D.1, QUid.sau-2SY-1D and QUid.sau-SC-3D are novel QTLs. Kompetitive Allele Specific PCR (KASP) markers tightly linked to them were further investigated for developing near-isogenic lines (NILs) carrying the major loci. Furthermore, candidate genes at these intervals harboring major and stable QTLs were predicted, and they were associated with plant development and water transportation in most cases. Comparison of physical locations of the identified QTL on the ‘Chinese Spring’ reference genome showed that several QTLs including two major ones, QUid.sau-2CN-1D.1 and QUid.sau-2SY-1D, are likely allelic confirming their validity and effectiveness. The significant relationships detected between UID and other agronomic traits and a proper UID were discussed. Collectively, our results dissected the underlying genetic basis for UID in wheat and laid a foundation for further fine mapping and map-based cloning of these QTLs.